Quantitation, Absorption and Tissue Distribution of Coenzyme Q10 from Pak-wanban (Sauropus androgynus L. Merr.) Leaf and Its Antioxidant Activities - KETTAWAN, Aikkarach; WUNJUNTUK, Kansuda (Walailak Journal of Science and Technology (WJST), 2021)
Pak-wanban (Sauropus androgynus L. Merr.), a popular Thai vegetable, has been found to have a high content of Coenzyme Q10 (CoQ10), which is a powerful antioxidant. This study investigated the quantitation, absorption and tissue distribution of CoQ10 from raw and stir-fried Pak-wanban and its antioxidant activities in rats. Male Wistar rats (seven weeks old) were randomly grouped as follows: (1) control, (2) raw Pak-wanban powder of 0.5 mg CoQ10/kg/day, (3) stir-fried Pak-wanban powder of 0.5 mg CoQ10/kg/day, (4) stir-fried Pak-wanban powder of 1.0 mg CoQ10/kg/day, and (5) commercially CoQ10 supplement groups of 0.5 mg CoQ10/kg/day. The results found that stir-fried cooking did not significantly reduce the content of CoQ10 in the Pak-wanban leaves. After 3 weeks of experimentation, the level of CoQ10 in the plasma, liver and spleen was increased in all Pak-wanban groups when compared to the control group. The level of CoQ10 in the stir-fried Pak-wanban group was significantly higher than the raw Pak-wanban group but slightly lower than the CoQ10 supplement group. Liver alpha-tocopherol concentrations were markedly increased in rats that consumed a high dose of CoQ10 from stir-fried Pak-wanban of 1 mg of CoQ10/kg/day when compared with the control group. Plasma antioxidant activities (ORAC: FRAP: DPPH) were significantly increased in both groups of stir-fried Pak-wanban when compared with the control group. We concluded that CoQ10 in Pak-wanban could be well absorbed and improved the plasma antioxidant activities. Furthermore, cooking oil may increase the bioavailability of CoQ10 from vegetables. Therefore, it would be useful for vegetarian people.